A Brief Overview of the Preclinical and Clinical Radiobiology of Microbeam Radiotherapy. Issue 11 (November 2021) - Fukunaga, H.; Butterworth, K.T.; McMahon, S.J.; Prise, K.M.
Abstract: Microbeam radiotherapy (MRT) is the delivery of spatially fractionated beams that have the potential to offer significant improvements in the therapeutic ratio due to the delivery of micron-sized high dose and dose rate beams. They build on longstanding clinical experience of GRID radiotherapy and more recently lattice-based approaches. Here we briefly overview the preclinical evidence for MRT efficacy and highlight the challenges for bringing this to clinical utility. The biological mechanisms underpinning MRT efficacy are still unclear, but involve vascular, bystander, stem cell and potentially immune responses. There is probably significant overlap in the mechanisms underpinning MRT responses and FLASH radiotherapy that needs to be further defined.